An alternative modular 'click-SNAr-click' approach to develop subcellular localised fluorescent probes to image mobile Zn2+ . Issue 47 (17th October 2019) - Fang, Le; Trigiante, Giuseppe; Crespo-Otero, Rachel; Philpott, Michael P.; Jones, Christopher R.; Watkinson, Michael
Abstract : A modular 'bottom to top' synthesis of organelle targeted small molecule fluorescent probes for the detection of mobile zinc. Abstract : Zn 2+ is involved in a number of biological processes and its wide-ranging roles at the subcellular level, especially in specific organelles, have not yet been fully established due to a lack of tools to image it effectively. We report a new and efficient modular double 'click' approach towards a range of sub-cellular localised probes for mobile zinc. Through this methodology, endoplasmic reticulum, mitochondria and lysosome localised probes were successfully prepared which show good fluorescence responses to mobile Zn 2+ in vitro and in cellulo whilst a non-targeting probe was synthesized as a control. The methodology appears to have wide-utility for the generation of sub-cellular localised probes by incorporating specific organelle targeting vectors for mobile Zn 2+ imaging.